2021
DOI: 10.1155/2021/2466441
|View full text |Cite
|
Sign up to set email alerts
|

Reform of the Practice Teaching System of Entrepreneurship Education Based on 5G Fog Computing in Colleges and Universities

Abstract: Innovation is inevitable for economic development of the China and even the world, and entrepreneurship education is also an important topic for educators at home and abroad. It is an important issue for the sustainable development and effective operation of industry and education to establish an integrated support system of industry and education in universities. The purpose of this research is to analyze the reform of entrepreneurship education in the fusion of industrial education and university education a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Regulatory bodies can foster stakeholder collaboration, including industry players, academia, and standardization organizations 65 . By encouraging partnerships and cooperation, regulators promote the development of common standards and interoperability, which is vital for successfully implementing 5G technology.…”
Section: Literature Review With Hypothesis Developmentmentioning
confidence: 99%
“…Regulatory bodies can foster stakeholder collaboration, including industry players, academia, and standardization organizations 65 . By encouraging partnerships and cooperation, regulators promote the development of common standards and interoperability, which is vital for successfully implementing 5G technology.…”
Section: Literature Review With Hypothesis Developmentmentioning
confidence: 99%
“…Developing countries can tap the potential of 5G technologies by concentrating on the application layer in areas of their current economic activities [76], [77]. Additionally, tertiary education institutions are collaborating with communication companies in equipping graduates with technical expertise and entrepreneurial skills in 5G technology standards and use cases [78]. Thus, 5G could play a vital role in transforming education, including: 5G technology for AR and VR in education [79]; development of mobile applications that use VR for education [80]; sharing of online curriculum resources based on 5G and IoT [81]; and so forth.…”
Section: A Mobile Industry Goals For 5g Networkmentioning
confidence: 99%
“…Liu, F. et al combined interviews and literature analysis to sort out the current situation and concepts of university industry-teaching integration, educational facilities, entrepreneurship education, etc., and found that the proposed reform of entrepreneurship education of industry-academia-research can better improve the current situation of employment of students in colleges and universities, but there still exist some problems such as the colleges and universities are not well adapted to this model at present, etc. [9]. Boqijonovich, I.…”
Section: Introductionmentioning
confidence: 99%